Familiares de pessoas portadoras de transtorno mental: conhecimento dos direitos à saúde - Moreno, Vania [UNESP] (2015)
The objective of this investigation was to understand what family members know about the rights of individuals aff ected by mental illness. To this end, a qualitative exploratory study was conducted. A semi-structured interview was used for data collection. Eighteen family members were interviewed at a psychosocial care center (CAPS) and a civil society organization (CSO) located in a municipality in the state of São Paulo, Brazil, between March and September 2013. Data were analyzed using thematic content analysis and the following categories were constructed: mental health services and the rights of individuals aff ected by mental illness. We were able to infer that in addition to drug-based therapy, mental health services must provide therapeutic activities. Family members of those aff ected by mental illness were unaware of the Brazilian Psychiatric Reform Law and mentioned the following rights: welfare benefi ts, free public transport, basic food basket and medications.